Ankle joint pressure changes in high tibial and distal femoral osteotomies: a cadaver study. Issue 1 (January 2017) - Krause, F.; Barandun, A.; Klammer, G.; Zderic, I.; Gueorguiev, B.; Schmid, T.
Abstract : Aims: To assess the effect of high tibial and distal femoral osteotomies (HTO and DFO) on the pressure characteristics of the ankle joint. Materials and Methods: Varus and valgus malalignment of the knee was simulated in human cadaver full-length legs. Testing included four measurements: baseline malalignment, 5° and 10° re-aligning osteotomy, and control baseline malalignment. For HTO, testing was rerun with the subtalar joint fixed. In order to represent half body weight, a 300 N force was applied onto the femoral head. Intra-articular sensors captured ankle pressure. Results: In the absence of restriction of subtalar movement, insignificant migration of the centre of force and changes of maximal pressure were seen at the ankle joint. With restricted subtalar motion, more significant lateralisation of the centre of force were seen with the subtalar joint in varus than in valgus position. Changes in maximum pressure were again not significant. Conclusion: The re-alignment of coronal plane knee deformities by HTO and DFO altered ankle pressure characteristics. When the subtalar joint was fixed in the varus position, migration of centre of force after HTO was more significant than when the subtalar joint was fixed in valgus. Cite this article: Bone Joint J 2017;99-B:59–65.